Human-centricity in AI governance: A systemic approach - Sigfrids, Anton; Leikas, Jaana; Salo-Pöntinen, Henrikki; Koskimies, Emmi (Frontiers in Artificial Intelligence, 2023)
Human-centricity is considered a key property in the development and governance of artificial intelligence (AI). Various strategies and guidelines highlight the concept as a key goal. However, they seem to refer to human-centricity only superficially, narrowing the concept to stand for the realization of human rights. The concept lacks substantial meaning and thus potency to influence steering mechanisms in society. In this article, we look at the ways to govern the development and utilization of AI in a truly human-centric way, and discuss governance modalities for enhancing ethical and social sustainability when applying AI. We discuss trust, communication and transparency as key prerequisites for governing sustainable human-centered AI in society, and collaborative policies that can contribute to the increase in trust in civil society. Finally, we introduce a systemic approach to ethically and socially sustainable, human-centered AI development and deployment.